2000
DOI: 10.1128/aac.44.3.697-704.2000
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Lumefantrine (Benflumetol) in Acute Falciparum Malaria

Abstract: The objective of this study was to conduct a prospective population pharmacokinetic and pharmacodynamic evaluation of lumefantrine during blinded comparisons of artemether-lumefantrine treatment regimens in uncomplicated multidrug-resistant falciparum malaria. Three combination regimens containing an average adult lumefantrine dose of 1,920 mg over 3 days (four doses) (regimen A) or 2,780 mg over 3 or 5 days (six doses) (regimen B or C, respectively) were given to 266 Thai patients. Detailed observations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
261
3
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(279 citation statements)
references
References 18 publications
13
261
3
2
Order By: Relevance
“…24 Although a previous study in Thailand reported a Day 7 blood lumefantrine concentration cut-off point of 331 nmol/l (175 ng/ml), 25 another study in Malawi reported patients were cured even below this level. 24 The difference might be explained by possible variations in food intake, 26 as the levels of lumefantrine blood concentrations may increase 16-fold in patients who took the drug with fatty food compared with without fat. 27,28 Age-based dosage schedules of ALu might also explain the unpredictable blood concentrations of lumefantrine, since the dose per kg may vary widely between patients, as reported for the CQ/SP combination.…”
Section: Discussionmentioning
confidence: 99%
“…24 Although a previous study in Thailand reported a Day 7 blood lumefantrine concentration cut-off point of 331 nmol/l (175 ng/ml), 25 another study in Malawi reported patients were cured even below this level. 24 The difference might be explained by possible variations in food intake, 26 as the levels of lumefantrine blood concentrations may increase 16-fold in patients who took the drug with fatty food compared with without fat. 27,28 Age-based dosage schedules of ALu might also explain the unpredictable blood concentrations of lumefantrine, since the dose per kg may vary widely between patients, as reported for the CQ/SP combination.…”
Section: Discussionmentioning
confidence: 99%
“…6 The World Health Organization's (WHO) recommendation of artemether-lumefantrine as first-line therapy for acute falciparum malaria in endemic areas 7 has led to widespread use of this fixed-dose combination in tablets, dispersible tablets (DTs), and powders meant for reconstitution into pediatric suspensions (PSs). Some studies have reported methods for the quantification of only artemether 8,9 or lumefantrine 10,11 in pharmaceutical and biological matrices. A few methods have been published for the simultaneous determination of artemether and lumefantrine in biological 3,12 and drug formulation matrices.…”
Section: Introductionmentioning
confidence: 99%
“…A few methods have been published for the simultaneous determination of artemether and lumefantrine in biological 3,12 and drug formulation matrices. 10,11 In 2011, Cesar and others 13 improved a method developed by Hodel and others 12 using liquid chromatography tandem mass spectrometry for the simultaneous quantification of artemether and lumefantrine of 14 antimalarials in human plasma, by eliminating a sample drying step and reducing the total chromatogram run time. Cesar and others in 2008 developed a method for the simultaneous quantification of artemether and lumefantrine in fixed-dose combination tablets using high-performance liquid chromatography (HPLC) with ultraviolet (UV) detection.…”
Section: Introductionmentioning
confidence: 99%
“…13 Lumefantrine oral bioavailability increases significantly if administered after a meal rich in fat and may be poor in acute malaria infection where nausea, vomiting and poor food intake are present. Pharmacists can educate and encourage patients to take their tablets with food or milk (if appetite is severely affected during acute infection).…”
Section: Discussionmentioning
confidence: 99%